Simulation of Dungdo Reservoir Water Distribution for Irrigation and Raw Water - Pratiwi, Sekar Arum; Sobriyah, Sobriyah; Setyawan, Ary (Journal La Multiapp, 2025)
Small reservoirs are structures that function to accommodate excess water during the rainy season so that it can be used during the dry season. Dungdo Reservoir is expected to help meet the needs of irrigation water and raw water for livestock in the surrounding community. Water distribution simulation aims to optimize water availability efficiently and evenly. The methodology used includes water balance analysis based on rainfall data, evapotranspiration, inflow, and changes in reservoir capacity. Irrigation water requirements are calculated based on the crop coefficient (Kc), while raw water requirements are calculated based on the number of livestock. Based on the simulation results with the existing planting pattern with an irrigation area of 171.60 Ha, it shows that the average water requirement is 279605.66 m3/15 days, while the reservoir's capacity to provide water is 53135.20 m3/15 days. The simulation results show that Dungdo Reservoir has not been able to optimally meet irrigation water and raw water needs.